(untitled) (Research, Society and Development, 2021)
This paper is an integrative literature review that aims to emphasize the main characteristics of using Digital Information and Communication Technologies (TDIC) to the pedagogical and didactic visual support in daily social context. Publications of the scientific community were consulted on the Medical Literature and Retrivial System onLine data base and on Caribean and Latin American Literature about Health Science, between 2010 and 2020. Eleven researches were selected to analysis and, among them, seven were obtained on International Periodicals. The review identified two conceptions about the deafness and how they are approached through time. The first, clinical and therapeutic, deals with the deafness diagnostic and with the deaf rehabilitation. The second, socioanthropological, deals with perceiving deafness as a cultural difference, not as a pathology. Thus, it was evident in this research that TDIC are used by two different perspectives, both with a focus on the quality of life of the deaf person. The first as didactic-pedagogical tools being a visual support for the deaf student and the other as a technology for the purpose of repairing the individual’s organic defect, deafness.